Kentucky's famous racehorses - Thompson, Patricia L. (Images of America., 2010)
"Central Kentucky is home to many magnificent horses and their farms. Although there are numerous places to witness these beautiful animals, including Keeneland, Churchill Downs, Pimlico, and Belmont, their history often gets overwhelmed by their statistics. [This book] goes beyond the numbers and provides insight into the character of these beloved creatures by featuring stories straight from those closest to the horses--the grooms"--P. [4] of cover.